Incidence and Predictors of Multiple Fractures Despite High Adherence to Oral Bisphosphonates: A Binational Population‐Based Cohort Study. (January 2016) - Hawley, Samuel; Javaid, M Kassim; Rubin, Katrine H; Judge, Andrew; Arden, Nigel K; Vestergaard, Peter; Eastell, Richard; Diez‐Perez, Adolfo; Cooper, Cyrus; Abrahamsen, Bo; Prieto‐Alhambra, Daniel
ABSTRACT: Oral bisphosphonates (BPs) are highly effective in preventing fractures and are recommended first‐line therapies for patients with osteoporosis. We identified the incidence and predictors of oral BP treatment failure, defined as the incidence of two or more fractures while on treatment (≥2 FWOT) among users with high adherence. Fractures were considered from 6 months after treatment initiation and up to 6 months after discontinuation. Data from computerized records and pharmacy invoices were obtained from Sistema d'Informació per al Desenvolupament de l'Investigació en Atenció Primària (SIDIAP; Catalonia, Spain) and Danish Health Registries (Denmark) for all incident users of oral BPs in 2006‐2007 and 2000‐2001, respectively. Fine and Gray survival models using backward‐stepwise selection (p‐entry 0.049; p‐ exit 0.10) and accounting for the competing risk of therapy cessation were used to identify predictors of ≥2 FWOT among patients having persisted with treatment ≥6 months with overall medication possession ratio (MPR) ≥80%. Incidence of ≥2 FWOT was 2.4 (95% confidence interval [CI], 1.8 to 3.2) and 1.7 (95% CI, 1.2 to 2.2) per 1000 patient‐years (PYs) within Catalonia and Denmark, respectively. Older age was predictive of ≥2 FWOT in both Catalonian and Danish cohorts: subhazard ratio (SHR) = 2.28 (95% CI, 1.11 to 4.68) and SHR = 2.61 (95% CI, 0.98 to 6.95), respectively, for 65 to <80 years; and SHR = 3.19 (95% CI, 1.33 to 7.69) and SHR = 4.88 (95% CI, 1.74 to 13.7), respectively, for ≥80 years. Further significant predictors of ≥2 FWOT identified within only one cohort were dementia, SHR = 4.46 (95% CI, 1.02 to 19.4) (SIDIAP); and history of recent or older fracture, SHR = 3.40 (95% CI, 1.50 to 7.68) and SHR = 2.08 (95% CI: 1.04‐4.15), respectively (Denmark). Even among highly adherent users of oral BP therapy, a minority sustain multiple fractures while on treatment. Older age was predictive of increased risk within both study populations, as was history of recent/old fracture and dementia within one but not both populations. Additional and/or alternative strategies should be investigated for these patients. © 2015 American Society for Bone and Mineral Research.